Kepuasan Remaja Terhadap Fungsi Keluarga Menurut Status Wilayah di Kabupaten Gunungkidul - Wiwik Puji Mulyani; Ari Yulianto (Jurnal Wanita dan Keluarga, 2023)
The phenomenon of early marriage in Gunungkidul Regency is adolescent problem which influenced by family functions. This research aims to analyze the implementation of family functions and the difference of high school adolescent’s satisfaction on family functions by the regional status. This research is a quantitative with survey methods. The sample of this research uses a quota sampling technique. Data acquisition through structured interviews. The results showed that the majority of respondents evaluated family function still below from their expectations, and there were no significant differences for satisfaction value by the regional status (Asymp. Sig 2-tailed = 0.310). Protection and economic functions have been optimal for rural families, meanwhile religion, protection, and socio-culture functions for urban families. Infrastructure development, technology capability, and good mobility have been the factors for family functions in rural and urban area inclined same.